Ginsenoside-Rb1 Attenuates Dilated Cardiomyopathy in cTnTR141W Transgenic Mouse - Haiping Zhao; Dan Lv; Wei Zhang; Wei Dong; Juan Feng; Zhiguang Xiang; Lan Huang; Chuan Qin; Lianfeng Zhang (Elsevier, 2010)
Familial dilated cardiomyopathy (FDCM) is caused by defective genes and specific medicines are not currently available to treat this. Ginsenoside-Rb1 provides cardioprotection in the experimental models of myocardial ischemia-reperfusion injury. Here we investigate Rb1's effect on DCM in cTnTR141W transgenic mouse. The transgene-positive mice aged 2 months were randomized into the model group and Rb1 [70 mg/(kg·day)] group; transgene-negative mice were used as a control. After 4-month treatment, cardiac function was assessed by echocardiography; cardiac tissues were prepared for histology and electron microscopy. Expression levels of molecular markers of cardiac hypertrophy, fibrosis, and intercalated disc proteins were detected by RT-PCR. Rb1 significantly decreased mortality, chamber dilation, and contractile dysfunction in cTnTR141W mice. Rb1 attenuated cardiac hypertrophy, interstitial fibrosis, ultrastructural degeneration, and intercalated disc remodeling in DCM hearts. Western blotting showed that Rb1 significantly decreased heparin-binding epidermal growth factor-like growth factor (HB-EGF) expression and signal transduction and activators of transcription 3 (STAT3) activation, which were gradually increased in DCM hearts. Our results showed that Rb1 clearly alleviated cardiac dysfunction and remodeling in the cTnTR141W transgenic mouse, indicating its potential utility in the treatment of FDCM. Keywords:: ginsenoside-Rb1, dilated cardiomyopathy, heparin-binding epidermal growth factor-like growth factor (HB-EGF), signal transduction and activators of transcription 3 (STAT3)